SUAR MODIFIKASI CUACA CoSAT 1000 AMAN TERHADAP STATUS MUTU AIR DANAU TOBA, SUMATERA UTARA: TINJAUAN STATUS MUTU AIR PADA PELAKSANAAN MODIFIKASI CUACA BERBASIS SUAR CoSAT-1000 DI DAERAH TANGKAPAN AIR DANAU TOBA - Dwipa Soehoed; Satyo Nuryanto; Ardila Yananto (BPPT, 2022)
Implementing Weather Modification Technology (TMC) using hygroscopic flare, which has chemical compounds Sodium Chloride as a hygroscopic seeding material, Potassium, Magnesium, etc., has been applied several times in TMC operations. For the first time, the hygroscopic flare was made by PT. Pindad, called Cloud Seeding Agent Tube 1000 (CoSAT 1000), has been used on TMC operation in Lake Toba Catchment Area to overcome Lake Toba's water deficit in 2021. To find out the impact that might be caused by the use of the CoSAT 1000, an analysis of the water parameter and quality has been carried out from samples of rainfall, river, and lake in the period before, during, and after the implementation of TMC activities. Based on the criteria for water quality standard requirements in Government Regulation number 22 of 2021 and Minister of Environment Guidelines for Determining Water Quality Status number 115 of 2003, the results obtained from the quality parameter test and water quality status that were taken have met the class 1 and 2 water quality standards, as well as with class A water quality status. It is concluded that the use of CoSAT-1000 flare seedlings in TMC operations does not have any negative impact on water quality status.